2017
DOI: 10.1177/0009922817702937
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Early Literacy Screening in Preschool Children

Abstract: The Early Literacy Screener (ELS) is a brief screen for emergent literacy delays in 4- and 5-year-olds. Standard developmental screens may also flag these children. What is the value of adding the ELS? Parents of children aged 4 (n = 45) and 5 (n = 26) years completed the Ages and Stages Questionnaire-3 (ASQ-3), the Survey of Well-Being in Young Children (SWYC), and the ELS. Rates of positive agreement (PA), negative agreement (NA), and overall agreement (Cohen's κ) across the various screening tools were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…15,16 We also showed that use of general developmental screeners, such as the Ages and Stages Questionnaire and the Survey of Well Being in Young Children, miss preschool children who have a delay in ELS. 17 In our sample, parents of 51% of the children who passed the Ages and Stages Questionnaire and 39% of those who passed the Survey of Well Being in Young Children had concerns about their child's ELS.…”
Section: T a G G E D P What's Newmentioning
confidence: 87%
“…15,16 We also showed that use of general developmental screeners, such as the Ages and Stages Questionnaire and the Survey of Well Being in Young Children, miss preschool children who have a delay in ELS. 17 In our sample, parents of 51% of the children who passed the Ages and Stages Questionnaire and 39% of those who passed the Survey of Well Being in Young Children had concerns about their child's ELS.…”
Section: T a G G E D P What's Newmentioning
confidence: 87%
“…North American publications using the SWYC scale report prevalence rates ranging from 28 to 47% for suspected cases of changes in social-emotional development. 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Com relação ao SWYC, é tido como um instrumento robusto, de triagem para detecção de alteração no desenvolvimento, comportamento e contexto familiar de crianças de 1 a 65 meses É extremamente útil na saúde primária e bastante necessário nas pesquisas que envolvem a saúde pública por serem úteis para identificação precoce de riscos na saúde da criança e da família (Chung et al2016;Iyer, Dawson, Sawyer, Abdullah, Saju & Needlman, 2017;Fierman et al 2016;Kurtz, Levine & Safyer 2017;Moreira 2016;Serres & Chen 2017;Whitesell, Sarche, & Trucksess, 2015).…”
Section: Discussionunclassified